Needs Analysis of Web-Based Counseling Guidance Applications in SMKN 6 Padang - Afif, Aqil; Mursyida, Lativa (Apik Cahaya Ilmu, 2025)
This research explores the condition of student counseling services at SMKN 6 Padang, which currently still relies on manual methods such as notebooks and Excel, risking data loss and inaccuracies. This research aims to identify the need for a web-based counseling application to improve data accuracy, expedite processes, and enhance accessibility for all stakeholders. Using qualitative methods, including observations and semi-structured interviews with guidance and counseling teachers, this research provides a comprehensive understanding of the existing system, its advantages, and its disadvantages. The findings indicate an urgent need for an integrated web-based application to address issues such as students' reluctance to seek counseling and inefficient documentation. The proposed solution includes an online platform for private consultations and efficient data management, which is expected to streamline the counseling process, improve data accuracy, and facilitate better communication between teachers, students, and parents. This research emphasizes the importance of utilizing technology to enhance the effectiveness of student counseling services.